Avaliação da acessibilidade ao emprego de individuos em condição de exclusão social - Segadilha dos Santos, Ana Beatriz Pereira (2021)
Every day people need to travel to participate in different activities spread around the city. If for any reason an individual is prevented from participating in their activities, in the intended and predetermined location, they may be considered socially excluded. The concept of accessibility can be used as a tool to measure social exclusion and identify the differences between the travel patterns of different groups. It is important to understand differences in accessibility levels to define urban planning processes and evaluate existing public policies, so that interventions in transport and land use measures can be elaborated considering social differences, mitigating inequalities in access to work. This paper evaluates the accessibility of job opportunities of three different groups, considering the level of social exclusion of workers in Recife, with feel transport and employment data. Six modes of transport and a combination of modes were considered for the analysis. The results showed that accessibility levels vary between social exclusion and the groups with low level of exclusion have 70% higher accessibility than groups with more excluded. The GIS analysis also identify the city areas and transport modes that have lower accessibility levels, this information can be used to elaborate land use and transport policies directed for require areas, to improve sustainable modes.